Health is wealth : health progrmme - Mackenzie, James; Haldane, William S. ([Scotland : Industrial Health Education Council], 1926)
1926 1926 1920s 16 pages 3 County. Both of these bodies are taking steps to secure grants from the Miners' Welfare Fund to cover programmes in these counties. It is expected that Cumberland and South and West Yorkshire will follow suit. In the North of England the programme will be largely among Miners, Railwaymen and Millworkers, though not exclusively. The North of England is the first part of the expansion, and it is intended to take the Midlands, London and District, and Wales and part of the West of England later, creating Executives in each district. From these Executives, and including Scotland, a General Council will be appointed. Much encouragement has been given to the Council by the Ministry of Health in this work, as the Ministry values its intensive and specialised nature, and also its voluntary basis. It has been possible to work the project on a comparatively small outlay, owing to the fact that the workers' organisations have co-operated with the Council in meeting local expenses, and also as the doctors have given their services without remuneration. The expenses for meetings for Miners have been met out of the grant of £400 by the Miners' Welfare Fund, but this is applicable to Scotland alone. A number of generous friends have given financial support and the Carnegie Trust gave a grant of £500 (in two instalments of £250 each), the Dental Board £100, and the Prudential Insurance Company £105. To all these the Council tenders its most grateful thanks. Considerable additional financial aid will be required to enable the work to be carried on, and to take advantage of the many openings being presented. The subject of health is in the air, and the amount of suffering from preventable sicknesses and diseases, with loss of time and production, induces the Council to view its propaganda as of the utmost importance and value to the country and alike to employers and employed. WM. S. HALDANE, Chairman. J. MACKENZIE, Secretary. 31st December, 1925. 200/B/3/2/C693/1/48